EDWARD SAID: THE POSTCOLONIAL THEORY AND THE LITERATURE OF DECOLONIZATION - Lutfi Hamadi (European Scientific Journal, ESJ, 2014)
This paper attempts an exploration of the literary theory of postcolonialism, which traces European colonialism of many regions all over the world, its effects on various aspects of the lives of the colonized people and its manifestations in the Western literary and philosophical heritage. Shedding light on the impact of this theory in the field of literary criticism, the paper focuses on Edward Said's views for the simple reason that he is considered the one who laid the cornerstone of this theory, despite the undeniable role of other leading figures. This theory is mainly based on what Said considers the false image of the Orient fabricated by Western thinkers as the primitive "other" in contrast with the civilized West. He believes that the consequences of colonialism are still persisting in the form of chaos, coups, corruption, civil wars, and bloodshed, which permeates many ex-colonies. The powerful colonizer has imposed a language and a culture, whereas those of the Oriental peoples have been ignored or distorted. Referring to some works of colonial and postcolonial novelists, the paper shows how being free from the repression of imperialism, the natives could, eventually, produce their own culture of opposition, build their own image, and write their history outside the frame they have for long been put into. With such writers, Conrad’s Heart of Darkness can never be read the same after Achebe’s criticism, nor can Bronte’s Jane Eyre after Jean Rhys’s postcolonial parallel novel Wide Sargasso Sea.